Sudden Cardiac Arrest Due to Subtotal Absence of Left‐sided Pericardium—Case Report and Review of the Literature. (14th June 2012) - Steinberg, Christian; Pelletier, Marie‐Josée; Perron, Jean; Kumar, Andreas; Champagne, Jean
Abstract Congenital absence of the pericardium is a very rare cardiac malformation, usually diagnosed fortuitously on autopsy or surgery. Symptoms related to these abnormalities are usually benign, and fatalities reported in the literature are almost exclusively secondary to herniation of the heart through a partial defect. We present the unusual case of a 44‐year‐old woman admitted for sudden cardiac arrest. Initial evaluation suggested acute anterior myocardial infarction, but further investigation ruled out coronary heart disease. No arrhythmia could be initiated on electrophysiological study, and absence of most of the left pericardium was confirmed by cardiac magnetic resonance imaging. After the exclusion of common etiologies such as idiopathic ventricular fibrillation, transient great vessel torsion due to hypermobility of the heart with secondary malignant arrhythmia was considered to be the most likely mechanism for the sudden cardiac arrest. A review of the available literature on clinical presentation, diagnostic tools, and therapeutic options is also presented.